The impact of administrative creativity on raising the job performance of administrative leaders in government institutions in the Sultanate of Oman - Abdul Muttalib, Mohamed Mihdar; Sulaiman, Ibrahim Fahad; ALharrasi, Muslem Salim Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
The study discussed the impact of administrative creativity to raise the job performance of administrative leaders in Al-Dakhliyah governorate in the Sultanate of Oman. The problem arose in the need to raise the job performance of administrative leaders, and to address the factors that led to it (originality and intellectual fluency), as it aimed to measure the extent of the impact of administrative creativity on the job performance of administrative leaders in government institutions in Al-Dakhliyah Governorate in the Sultanate of Oman. The study utilized the quantitative descriptive approach to achieve its goals and using the theory of creativity (Hang & Aiken, 1970) to reach the best expectation of job performance in return for provided incentives and promotions, qualification and training. A questionnaire was constructed for data collection, where it was built from (27) pharse, and a stratified sample of 280 respondents was obtained. The data were processed using multiple regression analysis, and the results have reached a direct impact of administrative creativity rate of (64.2%) among the administrative leader on job performance, and the most important recommendations are to conduct similar studies on other governorates that may face same challenges in job performance.
Keywords: administrative creativity; job performance; government institutions